Patch choice from a distance and use of habitat information during foraging by the parasitoid Ibalia leucospoides - Fischbein, Deborah (2012)
1. In environments in which resources are distributed heterogeneously, patch choice and the length of time spent on a patch by foragers are subject to strong selective pressures. This is particularly true for parasitoids because their host foraging success translates directly into individual fitness. 2. The aim of this study was to test whether: (i) females of the parasitoid Ibalia leucospoides (Hymenoptera: Ibaliidae) can discriminate among patches according to host numbers; (ii) the surrounding context affects the initial choice of patch, as well as time spent on patch; and (iii) the perceived quality of a given patch is affected by the quality of the surrounding patches. 3. Each female was randomly exposed to one of three different three-patch environments which differed in host number per patch, mean environment host number and host distribution among patches. For each treatment level, the first patch chosen and the time allocated to each patch visited by the female were recorded. 4. Females of I. leucospoides were able to discriminate different levels of host numbers among patches from a distance. The patch bearing the highest number of hosts was, predominantly, the first choice. Patch host number in association with mean habitat profitability influenced the length of time spent on the first patch visited. By contrast, variance in habitat profitability did not influence time allocation decisions. Contrary to the study prediction, there were no significant habitat-dependent time allocation differences among patches holding the same number of hosts. 5. The results indicate that, for I. leucospoides, patch exploitation decisions are partially influenced by information obtained from the habitat as a whole, a behaviour that may prove to indicate adaptive ability in highly patchy environments, as well as suggesting the presence of good cognitive abilities in this parasitoid species.